(untitled) (Nigerian Journal of Technology, 2018)
This study presents the influence of variability of Rice Husk Ash (RHA) on the geotechnical properties of subgrade. The subgrade soil classified as A–7–6 (Clayey soil) in the AASHTO Classification system or CL in the USCS was used. The RHA materials were obtained from Ebonyi, Enugu and Cross River States of Nigeria, respectively. The geotechnical properties investigated included consistency limits, compaction and the California Bearing Ratio (CBR) of the soil for varying RHA contents for the three different RHA sources. There was significant variability in the chemical composition of RHA, with samples from Cross River, Ebonyi and Enugu States having Silica contents of 84.55%, 76.30% and 70.12% respectively. The results obtained showed that there was a general increase in the Optimum Moisture Content (OMC) and CBR values of the soil with increase in RHA content. However, the plasticity and Maximum Dry Density (MDD) decreased with increase in RHA. http://dx.doi.org/10.4314/njt.v37i3.4